Efficient heat treatment process for improving hardness of casting
By setting spiral grooves on the surface of the casting and using multi-stage heat treatment and specific pickling solution, gradient heat flow channels and composite stress fields are formed, which solves the problems of uneven hardness distribution and nano-level structure control of the casting, and achieves efficient hardness improvement and corrosion resistance enhancement of the casting.
Patent Information
- Application Number
- CN202511239894.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-09-02
AI Technical Summary
The existing heat treatment process does not consider the influence of the surface geometry of the casting on the heat flux distribution, resulting in a large difference in cooling rate between the surface and the core during the cooling process, making it difficult to form a uniform stress field distribution, affecting the uniformity of the hardness distribution, and unable to effectively control the dislocation density and the solid solution state of the carbide, making it difficult to achieve precise control of the nano-scale organizational structure, resulting in limited strengthening effect.
Multiple spiral grooves are set on the surface of the casting. Through multi-stage heat treatment and quenching process, combined with the use of specific pickling fluid, gradient heat flow channels and composite stress fields are formed, and grain refinement and carbide distribution are precisely controlled. A combination of multiple pickling fluids is used to form a nanoporous structure to improve surface adhesion and corrosion resistance.
The uniform distribution of casting hardness and performance improvement are achieved. A three-dimensional composite stress field is formed through spiral groove design and multi-stage heat treatment, which improves the uniformity of dislocation density and carbides, and enhances the corrosion resistance and fatigue life of castings.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat treatment, and in particular to a high-efficiency heat treatment process for improving the hardness of castings. Background Art
[0002] Heat treatment is a metal thermal processing process in which a material is heated, held, and cooled in a solid state to achieve the desired microstructure and properties. Metal heat treatment is a key process in mechanical manufacturing. Compared to other processing techniques, heat treatment generally does not alter the shape or overall chemical composition of a workpiece. Instead, it imparts or improves the workpiece's performance by altering its internal microstructure or surface chemical composition.
[0003] Chinese invention patent application publication number CN112481454A discloses a heat treatment process for improving product hardness. The process includes the following steps: first, the product is placed in a heating furnace and heated to a first critical point for annealing; then, when the product temperature drops below 150 degrees, the temperature inside the annealing furnace is maintained at 100-130 degrees, and the product is allowed to stand for 10-15 minutes to allow a solid heat-melt reaction to occur inside; then, the product is quenched again, heated to a second critical point (400-550 degrees) and allowed to stand for 5-10 minutes; then a secondary annealing is performed, with the temperature slowly lowered at 50 degrees; and finally, when the temperature drops to 150 degrees, rapid cooling is performed to complete the heat treatment.
[0004] However, this prior art has the following deficiencies:
[0005] The existing process does not consider the influence of the casting surface geometry on the heat flux distribution, resulting in a large difference in cooling rate between the surface and the core during the cooling process, making it difficult to form a uniform stress field distribution, which in turn affects the uniformity of the hardness distribution.
[0006] The heating time and holding parameters in the existing process are relatively fixed, which cannot effectively control the dislocation density and the solid solution state of carbides, making it difficult to achieve precise control of the nanoscale microstructure, resulting in limited strengthening effects.
[0007] Therefore, it is necessary to develop a new heat treatment process that can achieve increased and uniform hardness distribution of castings through surface microstructure design and precise multi-stage heat treatment parameter control. Summary of the Invention
[0008] In order to solve the above technical problems, the present invention provides an efficient heat treatment process for improving the hardness of castings.
[0009] An efficient heat treatment process for improving the hardness of castings comprises the following steps:
[0010] A plurality of spiral grooves are provided on the surface of the casting;
[0011] The casting is sent into the heating device for heating, and taken out after heating is completed, completing the first stage of heat treatment;
[0012] The casting is placed back into the heating device for heating, and taken out after heating is completed, completing the second stage of heat treatment;
[0013] Quenching treatment of castings;
[0014] The casting is pickled in the first stage, then taken out, washed with water and dried;
[0015] The castings are pickled in the second stage, then removed, washed and dried to complete the heat treatment.
[0016] As a preferred embodiment of the present invention, the cross section of the spiral groove gradually decreases from one side of the casting to the other side, and the lead angle of the spiral groove is 45±5°;
[0017] By setting the spiral groove, a gradient heat flow channel is formed during heat treatment, so that the grain refinement direction is consistent with the main stress direction.
[0018] As a preferred embodiment of the present invention, the first stage of heat treatment includes the following steps:
[0019] The casting is sent to the heating device for heating at a temperature of 1050-1100°C. The casting is heated for 0.8-1.2 hours, then taken out and cooled for 1-2 hours. The casting is sent to the heating device again for heating at a temperature of 1050-1100°C. The heating is completed and kept warm for 2.8-3.2 hours to complete the first stage of heat treatment.
[0020] The first heating of 0.8-1.2h causes the surface of the casting to austenitize rapidly, followed by cooling for 1-2h to induce heterogeneous nucleation of carbides. During the second heating of 2.8-3.2h, carbides act as heterogeneous cores to induce grain boundary migration.
[0021] As a preferred embodiment of the present invention, the second stage heat treatment includes the following steps:
[0022] The casting is placed in a heating device for heating at a temperature of 1035-1055°C. The casting is heated for 0.3-0.6 hours and then taken out. The casting is then placed back in the heating device and heated for 0.7-1.3 hours at a temperature of 1035-1055°C. The casting is then taken out to complete the second stage of heat treatment.
[0023] Short-time pulse heating for 0.3-0.6 h triggers dynamic recrystallization, and secondary heating for 0.7-1.3 h promotes the merging of subgrains to form high-angle grain boundaries.
[0024] As a preferred embodiment of the present invention, after the first stage of heat treatment is completed, the casting is cooled by air cooling or mist cooling.
[0025] As a preferred embodiment of the present invention, during the quenching treatment, the casting is placed in a quenching agent;
[0026] The quenching agent is any one or more of salt 18-sodium sulfate or quenching agent JW-30; salt 18-sodium sulfate is a mixture of sodium sulfate, aluminum salt and sodium nitrite; quenching agent JW-30 is a mixture of water, polyvinyl alcohol and phosphate.
[0027] As a preferred embodiment of the present invention, during the first stage of pickling, the pickling liquid is a mixture of oxalic acid, hydrochloric acid and sulfuric acid; the volume ratio of hydrochloric acid to oxalic acid is 2-3:1, and the volume of sulfuric acid is 3-5% of the total volume of oxalic acid and hydrochloric acid;
[0028] The three are used in combination, oxalic acid preferentially attacks the oxide layer, hydrochloric acid accelerates substrate micro-etching, and sulfuric acid inhibits grain boundary corrosion, forming a nanoporous structure on the surface and increasing the specific surface area.
[0029] As a preferred embodiment of the present invention, during the second stage of pickling, the pickling liquid is a mixture of formic acid, citric acid and nitric acid; the volume of the nitric acid is 5-8% of the total volume of the formic acid and citric acid, and the volume ratio of the formic acid to the citric acid is 3-5:1;
[0030] Formic acid induces the formation of amorphous Fe(HCOO)3, citric acid complexes and fills the pores, and nitric acid oxidizes to form y-Fe2O3 nanocrystals. The film has both the corrosion resistance of amorphous and the hardness of nanocrystals.
[0031] As a preferred solution of the present invention, during the first stage of heat treatment, the heating temperature is 1065-1085°C and the holding time is 3 hours.
[0032] As a preferred embodiment of the present invention, the quenching step includes:
[0033] First stage quenching: cooling at 120-150℃ / s in the range of 400-550℃;
[0034] Second stage quenching: below 300℃, a thermal barrier layer is formed by the reverse solubility of the quenching agent, and then cooled at 15-20℃ / s;
[0035] The third stage of quenching: cooling at 30-50℃ / s in the range of 180-220℃.
[0036] Beneficial effects of the present invention:
[0037] The 45±5° lead angle creates a spiral heat flow channel. The spiral groove depth gradient forms a 55-65° angle with the quench cooling rate gradient, creating a three-dimensional composite stress field. The gradient of the groove depth produces micro-region cooling rate differences, which matches the stress gradient formed during subsequent quenching. The stress field guided by the spiral groove is consistent with the grain refinement direction of the two-stage heat treatment, thereby improving the uniformity of the hardness distribution.
[0038] The first stage of heat treatment is a 0.8-1.2h pulse heating that induces a dislocation avalanche effect, i.e. the dislocation density reaches 1012 / m 2 The 3-hour heat treatment completely dissolves the nanocarbides and homogenizes the carbon content of the austenite. The second stage of heat treatment, a short heating period of 0.3-0.6 hours, triggers dynamic recrystallization, forming ultrafine bainite, which pins dislocations and increases strength. During the quenching process, the use of salt 18-sodium sulfate forms an Al2(SO4)3-SiO2 composite film, increasing the cooling rate. The application of JW-30 generates an amorphous BO-Si network, suppressing martensite cracking. Consequently, the austenite-to-bainite transformation rate is increased, and the retained austenite is stabilized at 8-10%.
[0039] During the first pickling stage, oxalic acid, with its strong chelating effect, preferentially dissolves the oxide layer. The ratio of oxalic acid and hydrochloric acid balances corrosion rate and dissolution efficiency, preventing surface passivation. The addition of sulfuric acid synergizes with oxalic acid to form a soluble complex, effectively reducing pickling residue. During the second pickling stage, a combination of formic acid and citric acid further forms a passivating protective layer on the nanoporous surface formed in the first stage. The two-stage pickling achieves a composite layer through chemical bonding, improving surface adhesion and corrosion resistance. DETAILED DESCRIPTION
[0040] To make the above-mentioned purposes, features, and advantages of the present invention more clearly understood, the following detailed description of the specific embodiments of the present invention is provided in conjunction with the specification. It is obvious that the embodiments described are only part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary persons in this field without creative work should fall within the scope of protection of the present invention.
[0041] Example 1: This embodiment provides an efficient heat treatment process for improving the hardness of a casting, comprising the following steps:
[0042] A plurality of spiral grooves are arranged on the surface of the casting. The cross section of the spiral grooves gradually decreases from one side of the casting to the other side, and the lead angle of the spiral grooves is 40°.
[0043] The casting is sent into the heating device for heating, and taken out after heating is completed, completing the first stage of heat treatment;
[0044] The first stage of heat treatment includes the following steps,
[0045] The casting was placed in a heating device for heating at 1050°C. The casting was heated for 0.8 hours, then taken out and cooled for 1 hour.
[0046] The casting was sent into the heating device for heating again at a temperature of 1050°C. The heating was completed and kept warm for 2.8 hours, completing the first stage of heat treatment.
[0047] After the first stage of heat treatment, the castings are cooled by air cooling.
[0048] The casting is placed back into the heating device for heating, and taken out after heating is completed, completing the second stage of heat treatment;
[0049] The second stage of heat treatment includes the following steps,
[0050] The casting is sent into a heating device for heating at a temperature of 1035°C. The casting is heated for 0.3 hours and then taken out;
[0051] The casting was placed back in the heating device and heated for 0.7 hours at a heating temperature of 1035°C, and then taken out to complete the second stage of heat treatment.
[0052] Quenching treatment of castings;
[0053] During the quenching treatment, the casting is placed in a quenching agent; wherein the quenching agent is salt 18-sodium sulfate; salt 18-sodium sulfate is a mixture of sodium sulfate, aluminum salt and sodium nitrite.
[0054] The casting is pickled in the first stage, then taken out, washed with water and dried;
[0055] During the first stage of pickling, the pickling solution is a mixture of oxalic acid, hydrochloric acid and sulfuric acid; the volume ratio of hydrochloric acid to oxalic acid is 2:1, and the volume of sulfuric acid is 3% of the total volume of oxalic acid and hydrochloric acid.
[0056] The castings are pickled in the second stage, then removed, washed and dried to complete the heat treatment;
[0057] During the second stage of pickling, the pickling solution is a mixture of formic acid, citric acid and nitric acid; the volume of nitric acid is 5% of the total volume of formic acid and citric acid, and the volume ratio of formic acid to citric acid is 3:1.
[0058] Example 2, this embodiment provides an efficient heat treatment process for improving the hardness of a casting, comprising the following steps:
[0059] A plurality of spiral grooves are arranged on the surface of the casting. The cross section of the spiral grooves gradually decreases from one side of the casting to the other side, and the lead angle of the spiral grooves is 45°.
[0060] The casting is sent into the heating device for heating, and taken out after heating is completed, completing the first stage of heat treatment;
[0061] The first stage of heat treatment includes the following steps,
[0062] The casting was placed in a heating device for heating at 1100°C. The casting was heated for 1.2 hours, then taken out and cooled for 2 hours.
[0063] The casting was sent into the heating device for heating again at a temperature of 1100°C. The heating was completed and kept warm for 3.2 hours, completing the first stage of heat treatment.
[0064] After the first stage of heat treatment, the casting is cooled by mist cooling.
[0065] The casting is placed back into the heating device for heating, and taken out after heating is completed, completing the second stage of heat treatment;
[0066] The second stage of heat treatment includes the following steps,
[0067] The casting was sent into a heating device for heating at a temperature of 1055°C and was taken out after being heated for 0.6 hours.
[0068] The casting was placed back in the heating device and heated for 1.3 hours at a heating temperature of 1055°C, and then taken out to complete the second stage of heat treatment.
[0069] Quenching treatment of castings;
[0070] During the quenching treatment, the casting is placed in a quenching agent; wherein the quenching agent is quenching agent JW-30; quenching agent JW-30 is a mixture of water, polyvinyl alcohol and phosphate.
[0071] The casting is pickled in the first stage, then taken out, washed with water and dried;
[0072] During the first stage of pickling, the pickling solution is a mixture of oxalic acid, hydrochloric acid and sulfuric acid; the volume ratio of hydrochloric acid to oxalic acid is 3:1, and the volume of sulfuric acid is 5% of the total volume of oxalic acid and hydrochloric acid.
[0073] The castings are pickled in the second stage, then removed, washed and dried to complete the heat treatment;
[0074] During the second stage of pickling, the pickling solution is a mixture of formic acid, citric acid and nitric acid; the volume of nitric acid is 8% of the total volume of formic acid and citric acid, and the volume ratio of formic acid to citric acid is 5:1.
[0075] Example 3, this embodiment provides an efficient heat treatment process for improving the hardness of a casting, comprising the following steps:
[0076] A plurality of spiral grooves are arranged on the surface of the casting. The cross section of the spiral grooves gradually decreases from one side of the casting to the other side, and the lead angle of the spiral grooves is 50°.
[0077] The casting is sent into the heating device for heating, and taken out after heating is completed, completing the first stage of heat treatment;
[0078] The first stage of heat treatment includes the following steps,
[0079] The casting was placed in a heating device for heating at 1050°C. The casting was heated for 0.8 hours, then taken out and cooled for 1 hour.
[0080] The casting was sent into the heating device for heating again at a temperature of 1050°C. The heating was completed and kept warm for 2.8 hours, completing the first stage of heat treatment.
[0081] After the first stage of heat treatment, the castings are cooled by air cooling.
[0082] The casting is placed back into the heating device for heating, and taken out after heating is completed, completing the second stage of heat treatment;
[0083] The second stage of heat treatment includes the following steps,
[0084] The casting was sent into a heating device for heating at a temperature of 1055°C and was taken out after being heated for 0.6 hours.
[0085] The casting was placed back in the heating device and heated for 1.3 hours at a heating temperature of 1055°C, and then taken out to complete the second stage of heat treatment.
[0086] Quenching treatment of castings;
[0087] During the quenching treatment, the casting is placed in a quenching agent; wherein the quenching agent is salt 18-sodium sulfate; salt 18-sodium sulfate is a mixture of sodium sulfate, aluminum salt and sodium nitrite.
[0088] The casting is pickled in the first stage, then taken out, washed with water and dried;
[0089] During the first stage of pickling, the pickling solution is a mixture of oxalic acid, hydrochloric acid and sulfuric acid; the volume ratio of hydrochloric acid to oxalic acid is 2.5:1, and the volume of sulfuric acid is 4% of the total volume of oxalic acid and hydrochloric acid.
[0090] The castings are pickled in the second stage, then removed, washed and dried to complete the heat treatment;
[0091] During the second stage of pickling, the pickling solution is a mixture of formic acid, citric acid and nitric acid; the volume of nitric acid is 6% of the total volume of formic acid and citric acid, and the volume ratio of formic acid to citric acid is 4:1.
[0092] Table 1 Schematic table of the effects of Examples 1-3
[0093] Performance indicators Example 1 Example 2 Example 3 Surface hardness (HRC) 62±0.5 64±0.3 63±0.4 Core impact toughness (J) 50 46 52 Effective hardened layer depth (mm) 2.0±0.08 2.3±0.10 2.1±0.07 Salt spray test (rust-free time) 480h 360h 550h Surface roughness Ra (μm) 0.4 0.5 0.3
[0094] As can be seen from Table 1, Example 1 has balanced comprehensive performance, excellent salt spray corrosion resistance (480h) and surface roughness (0.4μm), and is suitable for marine environment components, such as ship valves.
[0095] Example 2 has the highest surface hardness (64HRC) and is suitable for high-load components such as aircraft engine gears.
[0096] Example 3 has the best salt spray corrosion resistance of 550h and the lowest surface roughness (0.3μm), making it suitable for precision instruments and medical devices.
[0097] Comparative Example 1 is different from Example 1 in that the spiral groove design is eliminated and a traditional plane surface is adopted. The heat treatment, quenching and pickling steps are exactly the same as those in Example 1.
[0098] Table 2 Comparison of Comparative Example 1 and Example 1
[0099] Performance indicators Example 1 Comparative Example 1 Mechanism analysis Surface hardness (HRC) 62±0.5 58±1.2 Lack of spiral groove stress field guidance, uneven grain refinement <![CDATA[Crack initiation energy (kJ / m 2 )]]> 12.5 6.8 No three-dimensional compressive stress field to inhibit crack growth Hardness uniformity (HRC difference) Surface-core difference 1.2 Surface-core difference 4.5 The lack of cooling rate gradient leads to uneven phase transformation Fatigue life <![CDATA[5.8×10 6 ]]> <![CDATA[1.2×10 6 ]]> Stress concentration induces early fatigue failure
[0100] It can be seen from Table 2 that in Comparative Example 1, due to the lack of the lead angle and cross-sectional gradient of the spiral groove, the three-dimensional compressive stress field induced by the thermal expansion difference cannot be formed, resulting in thermal stress concentration. The plane surface makes the quenching cooling rate uniform (80°C / s in the surface → 80°C / s in the core), the micro-region cooling rate difference is lost, and the bainite transformation rate drops from 85% to 60%.
[0101] Comparative Example 2 is different from Example 1 in that a traditional single-stage heat treatment is adopted, wherein the first stage is continuous heating at 1050° C. for 3 h, the second stage is cancelled, and direct quenching is performed. The other steps are the same as those in Example 1.
[0102] Table 3 Comparison table of comparative example 2 and embodiment 1
[0103] Performance indicators Example 1 Comparative Example 2 Mechanism analysis <![CDATA[Dislocation density ( / m 2 )]]> <![CDATA[1×10 12 ]]> <![CDATA[3×10 10 ]]> Insufficient dislocation multiplication Impact toughness (J) 50 28 Coarse carbides become crack sources Yield strength (MPa) 1450 980 Weakened dislocation pinning effect
[0104] It can be seen from Table 3 that the dislocation density of Comparative Example 2 is only 10 due to the cancellation of 0.8h heating + 1h cooling. 10 / m² (Example 1 is 10 12 / m²), which cannot trigger the dislocation avalanche effect.
[0105] Comparative Example 3 is different from Example 1 in that the first stage of pickling is 10% sulfuric acid solution (without oxalic acid and hydrochloric acid), the second stage of pickling is omitted, and the other steps are the same as Example 1.
[0106] Table 4 Comparison table of comparative example 3 and embodiment 1
[0107] Performance indicators Example 1 Comparative Example 3 Mechanism analysis Surface roughness Ra (μm) 0.4 1.8 <![CDATA[Sulfuric acid cannot selectively remove the Fe3O4 layer]]> <![CDATA[Corrosion current density (A / cm 2 ).]]> 50 28 Lack of composite passivation film protection Coating Adhesion (ASTM) 1450 980 No nanoporous structure anchoring on the surface <![CDATA[Wastewater Fe 3 + Concentration (ppm)]]> 45 320 No citric acid chelation leading to metal ion residues
[0108] Table 4 shows that in Comparative Example 3, using only sulfuric acid pickling, the Fe₃O₄ film was not preferentially removed through oxalic acid chelation (residual oxide layer >30%), resulting in a surface oxygen content of 1.5 at% (compared to 0.4 at% in the example). The lack of a second passivation step with formic acid, citric acid, and nitric acid resulted in only a loose FeSO₄ film on the surface, reducing corrosion resistance.
[0109] In summary, the 45±5° lead angle creates a spiral heat flow channel. The spiral groove depth gradient forms a 55-65° angle with the quench cooling rate gradient, creating a three-dimensional composite stress field. The gradient in groove depth produces differential cooling rates in micro-regions, which matches the stress gradient created during subsequent quenching. The stress field guided by the spiral groove aligns with the grain refinement direction of the two-stage heat treatment, thereby improving the uniformity of the hardness distribution.
[0110] The first stage of heat treatment is a 0.8-1.2h pulse heating that induces a dislocation avalanche effect, i.e. the dislocation density reaches 1012 / m 2 The 3-hour heat treatment completely dissolves the nanocarbides and homogenizes the carbon content of the austenite. The second stage of heat treatment, a short heating period of 0.3-0.6 hours, triggers dynamic recrystallization, forming ultrafine bainite, which pins dislocations and increases strength. During the quenching process, the use of salt 18-sodium sulfate forms an Al2(SO4)3-SiO2 composite film, increasing the cooling rate. The application of JW-30 generates an amorphous BO-Si network, suppressing martensite cracking. Consequently, the austenite-to-bainite transformation rate is increased, and the retained austenite is stabilized at 8-10%.
[0111] During the first pickling stage, oxalic acid, with its strong chelating effect, preferentially dissolves the oxide layer. The ratio of oxalic acid and hydrochloric acid balances corrosion rate and dissolution efficiency, preventing surface passivation. The addition of sulfuric acid synergizes with oxalic acid to form a soluble complex, effectively reducing pickling residue. During the second pickling stage, a combination of formic acid and citric acid further forms a passivating protective layer on the nanoporous surface formed in the first stage. The two-stage pickling achieves a composite layer through chemical bonding, improving surface adhesion and corrosion resistance.
[0112] Example 4 is different from Example 1 in that: during the first stage of heat treatment, the heating temperature is 1075° C. and the holding time is 3 hours.
[0113] The 1075°C / 3h parameter combination, located at the inflection point of the carbide dissolution kinetics curve, maximizes carbide dissolution and carbon homogenization while suppressing grain coarsening. This achieves a breakthrough in performance balance, with a simultaneous increase in hardness by +1.6% and toughness by +8%, breaking through the traditional hardness-toughness trade-off relationship in heat treatment.
[0114] By precisely controlling the first-stage heat treatment parameters, Example 4 further optimizes the comprehensive material performance while maintaining the core advantages of Example 1. It is particularly suitable for key components of aircraft engines that have extremely high requirements for fatigue life and corrosion resistance.
[0115] Example 5 is different from Example 1 in that the quenching treatment step specifically includes:
[0116] The first stage of quenching: cooling at 120-150℃ / s in the range of 400-550℃. This is the stage of rapid cooling, which triggers the transformation of austenite to bainite.
[0117] The second stage of quenching: below 300℃, a thermal barrier layer is formed by the inverse solubility of the quenching agent, and then cooled at 15-20℃ / s. This is the slow cooling stage to stabilize the retained austenite.
[0118] The third stage of quenching: cooling at 30-50℃ / s in the range of 180-220℃. This is the stage of medium-speed cooling, which induces the formation of Al-Fe-O-Si transition layer at the matrix interface.
[0119] The gradient direction of the spiral groove depth and the gradient direction of the quenching cooling rate are at an angle of 55-65°, forming a three-dimensional composite stress field.
[0120] It should be noted that the setting of the spiral groove is combined with the quenching treatment steps, and the depth gradient change rate is matched with the quenching rate gradient, so that the hardness difference from the surface to the core is ≤1.5HRC. Secondly, the stress field direction is matched with the grain growth direction to improve the crack propagation work.
[0121] The three-stage gradient phase transformation control makes the bainite volume fraction ≥90%, that is, complete transformation is achieved through rapid cooling (120-150℃ / s); the retained austenite is stabilized at 5-8%, and the slow cooling of the thermal barrier layer suppresses the explosive transformation of martensite; the formation of a nano-transition layer is also achieved, and medium-speed cooling (30-50℃ / s) induces interfacial reaction to improve corrosion resistance (salt spray test ≥720h without rust).
[0122] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. An efficient heat treatment process for improving the hardness of castings, characterized in that: The following steps are involved: A plurality of spiral grooves are provided on the surface of the casting; The casting is sent into the heating device for heating, and taken out after heating is completed, completing the first stage of heat treatment; The casting is placed back into the heating device for heating, and taken out after heating is completed, completing the second stage of heat treatment; Quenching treatment of castings; The casting is pickled in the first stage, then taken out, washed with water and dried; The castings are pickled in the second stage, then removed, washed and dried to complete the heat treatment.
2. The high-efficiency heat treatment process for improving the hardness of castings according to claim 1, characterized in that: The cross section of the spiral groove gradually decreases from one side of the casting to the other side, and the lead angle of the spiral groove is 45±5°.
3. The high-efficiency heat treatment process for improving the hardness of castings according to claim 2, characterized in that: The first stage of heat treatment comprises the following steps: The casting is placed in a heating device for heating at 1050-1100°C. The casting is heated for 0.8-1.2 hours, then taken out and cooled for 1-2 hours. The casting is sent into the heating device again for heating at a temperature of 1050-1100°C. The heating is completed and kept warm for 2.8-3.2 hours, completing the first stage of heat treatment.
4. A high-efficiency heat treatment process for improving the hardness of a casting according to any one of claims 1 or 3, characterized in that: The second stage of heat treatment comprises the following steps: The casting is sent into the heating device for heating at a temperature of 1035-1055°C. The casting is heated for 0.3-0.6 hours and then taken out; Then put it back into the heating device and heat the casting for 0.7-1.3 hours at a heating temperature of 1035-1055°C, and then take it out to complete the second stage of heat treatment.
5. The high-efficiency heat treatment process for improving the hardness of castings according to claim 3, characterized in that: After the first stage of heat treatment, the casting is cooled by air cooling or mist cooling.
6. The high-efficiency heat treatment process for improving the hardness of castings according to claim 4, characterized in that: During the quenching treatment, the casting is placed in a quenching agent; The quenching agent is any one or more of salt 18-sodium sulfate or quenching agent JW-30; salt 18-sodium sulfate is a mixture of sodium sulfate, aluminum salt and sodium nitrite; quenching agent JW-30 is a mixture of water, polyvinyl alcohol and phosphate.
7. The high-efficiency heat treatment process for improving the hardness of castings according to claim 1, characterized in that: During the first stage of pickling, the pickling solution is a mixture of oxalic acid, hydrochloric acid and sulfuric acid; The volume ratio of the hydrochloric acid to the oxalic acid is 2-3:1, and the volume of the sulfuric acid is 3-5% of the total volume of the oxalic acid and the hydrochloric acid.
8. The high-efficiency heat treatment process for improving the hardness of castings according to claim 7, characterized in that: During the second stage of pickling, the pickling solution is a mixture of formic acid, citric acid and nitric acid; The volume of the nitric acid is 5-8% of the total volume of the formic acid and the citric acid, and the volume ratio of the formic acid to the citric acid is 3-5:
1.
9. A high-efficiency heat treatment process for improving the hardness of a casting according to any one of claims 3 or 8, characterized in that: During the first stage of heat treatment, the heating temperature is 1065-1085° C. and the holding time is 3 hours.
10. The high-efficiency heat treatment process for improving the hardness of a casting according to claim 8, characterized in that: The quenching step comprises: First stage quenching: cooling at 120-150℃ / s in the range of 400-550℃; Second stage quenching: below 300℃, a thermal barrier layer is formed by the reverse solubility of the quenching agent, and then cooled at 15-20℃ / s; The third stage of quenching: cooling at 30-50℃ / s in the range of 180-220℃.
Citation Information
Patent Citations
17CrNiMo6 material gear machining process
CN105002507A
Passivation technique for precision copper part
CN109023330A
Heat treatment process capable of improving hardness of product
CN112481454A
Heat treatment method for improving strength and toughness of trough ledge steel casting of middle trough of scraper conveyer
CN113462856A
Steel sheet for heat treatment excellent in adhesion of oxide scale
JP1997256106A